Design of 2D Animation as an Educational Medium to Increase Saving Interest of Elementary School Students - Melly Angghita; Ade Moussadecq (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Paramadina, 2025)
This study aims to design and develop animation-based educational media as a means to support more interactive and engaging learning. The background of this research is based on the low learning interest of students when using only conventional methods such as lectures and static media. The method employed is Research and Development (R&D) with a multimedia design model, which includes the stages of analysis, design, production, and testing. The development process involves scriptwriting, character design, animation production, and integration into the educational media format. Validation by content and media experts indicated that the designed educational animation is highly feasible for use, with a feasibility percentage above 80%. Limited trials with students showed that this media can enhance learning interest, student engagement, and understanding of the learning material. Therefore, animation can be considered an innovative alternative learning medium to support the improvement of education quality.is study aims to design and develop animation-based educational media as a means to support more interactive and engaging learning. The background of this research is based on the low learning interest of students when using only conventional methods such as lectures and static media. The method employed is Research and Development (R&D) with a multimedia design model, which includes the stages of analysis, design, production, and testing. The development process involves scriptwriting, character design, animation production, and integration into the educational media format. Validation by content and media experts indicated that the designed educational animation is highly feasible for use, with a feasibility percentage above 80%. Limited trials with students showed that this media can enhance learning interest, student engagement, and understanding of the learning material. Therefore, animation can be considered an innovative alternative learning medium to support the improvement of education quality.